2014
DOI: 10.1152/ajpheart.00012.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase transgenic upregulation modulates basal cardiac performance and the response to ischemic stress in male mice

Abstract: Estrogen in females is conventionally considered a cardioprotective influence, but a role for estrogen in male cardioprotection has yet to be defined. Estrogen biosynthesis from testosterone is regulated by aromatase. Aromatase has recently been shown to be expressed in the adult heart, although little is known about its involvement in the regulation of myocardial function and stress responses. The goal of this study was to determine whether upregulation of tissue aromatase expression could improve ischemic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Although E-4031 10 mg/kg BW showed strong bradycardia (Table 2), aromatase knockout significantly decreased E-4031-induced QT C prolongation, indicating that ablation of endogenous estrogen affects E-4031 sensitivity. Recent data depict the importance of aromatase expression in the heart, which shows protective effects on ischemic myocardial cells and coronary vasculature damage (Bell et al, 2014;Jazbutyte et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although E-4031 10 mg/kg BW showed strong bradycardia (Table 2), aromatase knockout significantly decreased E-4031-induced QT C prolongation, indicating that ablation of endogenous estrogen affects E-4031 sensitivity. Recent data depict the importance of aromatase expression in the heart, which shows protective effects on ischemic myocardial cells and coronary vasculature damage (Bell et al, 2014;Jazbutyte et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies, no change was observed in the expression of NCX expression in both oestrogen treatment and OVX animals . Although oestrogen decreased the expression of PLB, and OVX increased its expression, no change in expression was found in other reports . On the other hand, oestrogen downregulated the RyR expression, while in other reports both OVX and oestrogen treatments had no effect on RyR expression .…”
Section: Ers and βArs As Coregulators Of Cardiac Ca2+‐handling Proteinsmentioning
confidence: 74%
“…Furthermore, treatment of E 2 and ERα attenuated isoproterenol-induced cardiac hypertrophy in H9c2 cells [9], indicating beneficial action of E 2 -induced cardioprotection. Moreover, overexpression of Aro improved functional recovery post-ischaemia in mice [10]. Although gonadal tissue is the main site for E 2 synthesis, locally E 2 production in extragonadal tissues such as heart and brain likely has a specific role on these organs.…”
Section: Introductionmentioning
confidence: 94%